Combinatorial IL-17RB, ST2, and TSLPR Signaling in Dendritic Cells of Patients With Allergic Rhinitis - Zheng, Rui; Chen, Yang; Shi, Jianbo; Wang, Kai; Huang, Xuekun; Sun, Yueqi; Yang, Qintai (Frontiers in Cell and Developmental Biology, 2020)
Objectives: Myeloid dendritic cells (DCs) in patients with allergic rhinitis (AR) express higher levels of IL-17RB, ST2, and TSLPR. However, their functional roles in DCs are much less clear. This study aimed to determine the combined effects of these three receptor signals on the T cell-polarising function of DCs in AR patients. Methods: Monocyte-derived DCs (mo-DCs) were generated and stimulated with Toll-like receptor (TLR) 1–9 ligands. Der.p1-induced mo-DCs were stimulated with different combinations of IL-25, IL-33, and TSLP to determine phenotypic characteristics and then co-cultured with CD4+ T cells to assess Th2 cytokine production. Expression levels of IL-17RB, ST2, and TSLPR on myeloid DCs (mDCs) from peripheral blood of AR and healthy subjects were detected to confirm the association of these receptors with disease severity. Results: TLR ligands induced AR-derived mo-DCs to increase IL-17RB, ST2, and TSLPR expression by varying degrees; among these, Der.p1 was the strongest inducer. Der.p1-induced mo-DCs from AR showed increased OX40L expression. IL-25, IL-33, and TSLP (alone or in double combination) significantly increased OX40L expression on Der.p1-induced mo-DCs from AR, thereby increasing the production of IL-4, IL-5, and IL-13 in co-cultured CD4+ T cells; triple combination further enhanced these effects. The percentage of IL-17RB+ST2+TSLPR+ mDCs was increased in AR, higher in moderate to severe phase than in mild phase, and positively correlated with the percentages of IL-4+, IL-5+, and IL-13+ T cells. Conclusion: A combination of IL-17RB, ST2, and TSLPR signals amplified the Th2-polarising function of DCs and was associated with disease severity in AR patients.